2013
DOI: 10.1517/17425255.2013.823400
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic considerations of drugs in the treatment of allergic diseases

Abstract: Most drugs used in allergic diseases are extensively metabolized. Drug interaction or adverse reactions related to altered metabolism are relevant issues that should be considered in the management of allergic diseases. However, much additional research is required before defining pharmacogenomic biomarkers for the management of drugs used in allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Impaired metabolism may cause drug accumulation with the associated adverse effects or it may cause therapeutic failure if prodrugs are not efficiently converted to their active forms. It has been shown that diverse Cytochrome P450 enzymes are involved in the metabolism of formoterol, and CYP3A4 and CYP3A5 are involved in the hydroxylation of salmeterol (revised in García-Martín et al, 2013). In this respect, CYP3A5 is the principal CYP3A form in the lung (Kivistö et al, 1996), and since the above-mentioned drugs suffer pre-systemic metabolism, it is plausible that patient carriers of the gain-of-function CYP3A5 * 1 allele may have lower bioavailability, or lower therapeutic efficacy, or apparent resistance, to inhaled drugs that are CYP3A substrates, but further studies to confirm this hypothesis are necessary (García-Martín et al, 2013).…”
Section: Drugs Used In Asthma Treatmentmentioning
confidence: 99%
“…Impaired metabolism may cause drug accumulation with the associated adverse effects or it may cause therapeutic failure if prodrugs are not efficiently converted to their active forms. It has been shown that diverse Cytochrome P450 enzymes are involved in the metabolism of formoterol, and CYP3A4 and CYP3A5 are involved in the hydroxylation of salmeterol (revised in García-Martín et al, 2013). In this respect, CYP3A5 is the principal CYP3A form in the lung (Kivistö et al, 1996), and since the above-mentioned drugs suffer pre-systemic metabolism, it is plausible that patient carriers of the gain-of-function CYP3A5 * 1 allele may have lower bioavailability, or lower therapeutic efficacy, or apparent resistance, to inhaled drugs that are CYP3A substrates, but further studies to confirm this hypothesis are necessary (García-Martín et al, 2013).…”
Section: Drugs Used In Asthma Treatmentmentioning
confidence: 99%
“…Regarding Phase II enzymes, the most relevant in terms of percentage of drugs metabolized are UDP-glucuronyltransferases (UDPs), glutathione S -transferases (GSTs), sulphotransferases (SULTs), and N -acetyltransferases (NATs) particularly NAT2 ( Evans and Relling, 1999 ). Drugs belonging to many pharmacological groups are affected by polymorphic metabolism mediated by these enzymes, including for instance anesthetics, anti-Parkinson’s disease drugs, antihistamine drugs, antipsychotics, narcotics, or antidepressants; specific recommendations for the use of these drugs in the context of variability in drug metabolism have been published ( Restrepo et al, 2009 ; Khokhar and Tyndale, 2011 ; Relling and Klein, 2011 ; Swen et al, 2011 ; Agundez et al, 2013 ; Garcia-Martin et al, 2013 ).…”
Section: Enzymes That Metabolize Cns Drugsmentioning
confidence: 99%
“…It is metabolized in the liver by oxidative processes, excreted mainly in the feces. Less than 5% of the drug (in the form of the parent substance or metabolites) is excreted in the urine [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Praziquantel is metabolized in the liver by CYP3A enzymes to metabolites, the activity of which is not known. It is excreted mainly in the urine [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%